Wave energy converter physical model design and testing: The case of floating oscillating-water-columns. (15th November 2020) - Portillo, J.C.C.; Collins, K.M.; Gomes, R.P.F.; Henriques, J.C.C.; Gato, L.M.C.; Howey, B.D.; Hann, M.R.; Greaves, D.M.; Falcão, A.F.O.
Abstract: The quest for exploiting the ocean resources and understanding its behaviour has been a challenge with increasing needs for innovation and technology. Model testing is an essential step in offshore renewable energy technology development. It involves challenges that require experience and guidance. Costly mistakes might arise with the subsequent waste of time and resources. This paper presents the model design and testing processes as part of wave energy projects and the results of experimental testing of two types of oscillating-water-column (OWC) wave energy converters (WEC). The model design aims at the creation of a reduced-scale model to simulate the physical phenomena found in full-scale devices. It is a process that requires several skills and an adequate compromise among all variables. This design involves several approaches as different physical phenomena do not follow the same similarity conditions, requiring adjustments in scale, materials, and other relevant properties. Besides, the model testing process comprises the necessary planning and actions to execute the tests and post-processing of data. This process is addressed here through model design and testing of two WECs: the coaxial-duct and the spar-buoy OWCs. The configurations have been designed and studied for large-scale energy production and small-scale power in oceanographic applications. Although the devices are both OWCs, the designs exhibit significant differences. The development process of the models and results are presented for the two OWC devices. Free-decay tests, hydrodynamic performance and mooring tension results are presented and discussed. These may serve as guidelines and numerical modelling validation. Highlights: Wave energy converters model design and testing processes are addressed. Physical model conception and verification are discussed. The methodology is illustrated with two floating oscillating-water-columns devices. Experimental results were obtained for regular and irregular waves. Mooring loads were measured under survivability testing conditions.